Kynurenic Acid Levels in Cerebrospinal Fluid from Patients with Alzheimer's Disease or Dementia with Lewy Bodies. (January 2014) - Wennström, Malin; Nielsen, Henrietta M; Orhan, Funda; Londos, Elisabet; Minthon, Lennart; Erhardt, Sophie
Kynurenic acid (KYNA) is implicated in cognitive functions. Altered concentrations of the compound are found in serum and cerebrospinal fluid (CSF) of patients with Alzheimer's disease (AD). Further studies to determine whether KYNA serves as a biomarker for cognitive decline and dementia progression are required. In this study, we measured CSF KYNA levels in AD patients (n = 19), patients with dementia with Lewy bodies (DLB) (n = 18), and healthy age-matched controls (Ctrls)) (n = 20) to further explore possible correlations between KYNA levels, cognitive decline, and well-established AD and inflammatory markers. Neither DLB patients nor AD patients showed significantly altered CSF KYNA levels compared to Ctrls. However, female AD patients displayed significantly higher KYNA levels compared to male AD patients, a gender difference not seen in the Ctrl or DLB group. Levels of KYNA significantly correlated with the AD-biomarker P-tau and the inflammation marker soluble intercellular adhesion molecule-1 (sICAM-1) in the AD patient group. No associations between KYNA and cognitive functions were found. Our study shows that, although KYNA was not associated with cognitive decline in AD or DLB patients, it may be implicated in AD-related hyperphosphorylation of tau and inflammation. Further studies on larger patient cohorts are required to understand the potential role of KYNA in AD and DLB.